Measuring Patient Experience: Concepts and Methods - Ahmed, Faraz; Burt, Jenni; Roland, Martin (The patient : patient-centered outcomes research, 2014)
Providing a good patient experience is a key part of providing high-quality medical care. This paper explains why patient experience is important in its own right, and its relationship to other domains of quality. We describe methods of measuring patient experience, including issues relating to validity, reliability and response bias. Differences in reported patient experience may sometimes reflect differences in expectations of different population groups and we describe the arguments for and against adjusting patient experience data for population characteristics. As with other quality improvement strategies, feeding back patient experience data on its own is unlikely to improve quality: sustained and multiple interventions are usually required to deliver sustained improvements in care.